Trilingual-Based Instruction in English for Tourism: Empowering Students with Cultural Knowledge and Communication Competence - Taula'bi, Nilma; Yakub Tangdibiri; Markus Deli Girik Allo; Dimas Rio (Universitas Sulawesi Barat, 2025)
This study holds significant urgency in the context of language learning development and the enhancement of students’ communication skills, aiming to prepare high-quality and competitive human resources for the workforce—particularly in the tourism sector. Additionally, the study serves as a preventive effort to ensure that younger generations are still informed about, take pride in, and can preserve and promote the rich cultural heritage of Toraja. In this regard, the implementation of the trilingual method in the English for Tourism course is expected to help both lecturers and students in the English Language Education Study Program at Universitas Kristen Indonesia (UKI) Toraja. The primary aim of this study is to investigate the implementation of the trilingual method in the English for Tourism course. This research employs a qualitative approach using a descriptive qualitative design. The findings show that the trilingual method is implemented through five main activities: the integration of Toraja local culture into the learning materials, simulation-based learning, fieldwork projects, translation of cultural texts, and the production of trilingual tourism promotional video.